Human Herpesvirus 8 in Perinatally HIV-infected Children with Interstitial Lung Disease. (20th November 2017) - Scotta, Marcelo Comerlato; Fabro, Alexandre Todorovic; Machado, Paula Renata Lima; Ramos, Simone Gusmão; Cervi, Maria Célia; da Fonseca, Benedito Antônio Lopes; Motta, Fabrizio; Negrini, Bento Vidal de Moura
ABSTRACT: Introduction: Human herpesvirus 8 (HHV-8) is associated with the pathogenesis of Kaposi Sarcoma and interstitial pneumonitis in adults. This study aims to evaluate association between HHV-8 and interstitial lung disease in HIV-infected children. Methods: HIV-infected children with interstitial pneumonitis underwent lung biopsies in a tertiary hospital and were investigated for HHV-8, Epstein-Barr virus (EBV) and cytomegalovirus (CMV) using polymerase chain reaction (PCR) and immunohistochemistry in lung tissue. Peripheral blood PCR was also performed for HHV-8. Results: From six patients included, PCR for HHV-8 was positive in lung samples in four children and in peripheral blood in one. PCR for EBV and CMV and immunohistochemical study for HHV-8, EBV and CMV in lung were negative in all patients. Conclusion: No previous cases of HHV-8-associated interstitial pneumonitis was described in HIV-infected children. An immunological disorder and an infectious agent might influence development of the lymphoid interstitial pneumonitis. HHV-8 may be this infectious trigger.